2019
DOI: 10.4191/kcers.2019.56.6.05
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Kaolinite as a Raw Material for Porcelain

Abstract: In this work, we investigated kaolinite raw materials from China, Vietnam, and Seongju (Korea) used for the manufacture of porcelain products in Korea. According to chemical analysis results, for the kaolinites from Seongju, more feldspar components containing CaO, K 2 O, and Na 2 O are found than in those from China or Vietnam, of which the composition is close to that of pure kaolinite. Through X-ray Rietveld quantitative analysis, kaolinite and muscovite are found to be the main phases for all the raw mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In a second stage, 25% addition of recycled alumina (silico-aluminous refractory brick waste) in the aforementioned mixture and sintering at 1500 °C further improved the mechanical properties of the new ceramic, especially its flexular strength value (45.08 MPa), due mainly to the high content of mullite which occurred in the refractory waste and its elongated crystal shape. At that time, because of the significant reduction in the kaolin deposits in Korea used in porcelain production, Kim and Hwang [ 55 ] investigated alternative clays derived from China and Vietnam. They indicated that the whole raw materials studied (Korea, China, Vietnam) were comprised mainly of kaolinite and muscovite and less of halloysite, quartz and rutile.…”
Section: Summarizing Papers and Discussionmentioning
confidence: 99%
“…In a second stage, 25% addition of recycled alumina (silico-aluminous refractory brick waste) in the aforementioned mixture and sintering at 1500 °C further improved the mechanical properties of the new ceramic, especially its flexular strength value (45.08 MPa), due mainly to the high content of mullite which occurred in the refractory waste and its elongated crystal shape. At that time, because of the significant reduction in the kaolin deposits in Korea used in porcelain production, Kim and Hwang [ 55 ] investigated alternative clays derived from China and Vietnam. They indicated that the whole raw materials studied (Korea, China, Vietnam) were comprised mainly of kaolinite and muscovite and less of halloysite, quartz and rutile.…”
Section: Summarizing Papers and Discussionmentioning
confidence: 99%